Analisis Keoptimalan Fungsi Baitul Maal Pada Lembaga Keuangan Mikro Islam (Studi Kasus Pada BMT Nurul Jannah di Gresik dan BMT Muda di Surabaya) - Azizah, Rana Ayu; Suprayogi, Noven (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Basically Baitul Maal wa tamwil (BMT) have to run optimally both their business functions (Baitul tamwil) and social functions (Baitul Maal). Optimal can be seen from how the organization runs their operations effectively and efficiently. The aim of this research was to determine what causes of less-optimal from the social functions (Baitul Maal) on BMT.This research used qualitative approach and case study method with explanatory study. The informants in this research were managers and administrators of BMT. Based on that method, the selected informants were executive manager of BMT, menager of Baitul Maal, and management of BMT. Data collected by interviews with informants using validation method of sources and data triangulation.The results of this research indicate that their motivation cause disoptimal Baitul Maal function at Islamic microfinance institutions (case study at BMT Nurul Jannah Gresik and BMT Muda Surabaya).